STRATEGI PESAN INSTAGRAM "GREENPEACE" SEBAGAI MEDIA KAMPANYE PENGURANGAN SAMPAH PLASTIK - Diah Ayu Wulandari (2020)
This research contains about Greenpeace's Instagram message strategy in campaigning for plastic waste demand. This research was conducted based on the increasing number of Instagram social media users and the use of plastic materials every year in Indonesia. The purpose of this study is to use Instagram social media to help transport plastic or use plastic materials. In addition, to find out what is the reason for Greenpeace (Non-Governmental Organizations) working in this environment, use Instagram as a medium to campaign or encourage plastic waste relief. This study was presented using qualitative methods, research data obtained by observation and interviews conducted by researchers directly with speakers, namely Digital Specialists, Urban Campaigns and Volunteers from Greenpeace. The results of this study are the results of interviews with informants and are effective from social media whether in campaigning for Plastic Waste Reduction.